In vitro antimicrobial and antioxidant activities of bioactive compounds (secondary metabolites) extracted from Streptomyces lydicus A2 - Monthon Lertcanawanichakul, Kanchanat Pondet, Jutaporn Kwantep (Journal of Applied Pharmaceutical Science, 2015)
In the present study, we report antibacterial and antioxidant activities of bioactive compounds extracts (ethyl acetate extract, methanolic extract, n-hexane extract) of Streptomyces lydicus A2 isolated from air in Sciencetific and Technological Equipments Building, Walailak University, Thailand. The S. lydicus A2 is potential to produce bioactive compounds showed various biological activities. In previous research, its culture broth or extract shows antimicrobial activity. In this study, extract prepared from S. lydicus A2 stored at -80 oC was re-evaluated the antimicrobial activity when grew in various medium and incubation time to find out storage effect towards the antimicrobial activity. The extract (fractions) from S. lydicus A2 still inhibit test bacteria even though it decreases 50% than the extract prepared from S. lydicus A2 without -80 oC storage. Antimicrobial activity against Staphylococcus aureus and Bacillus cereus was only exhibited by the methanolic fraction S. lydicus A2. Only, the ethyl acetate extract was found to possess dose dependent DPPH free radical scavenging. The isolate A2 could be a potential candidate for the development of novel therapeutic agents active against pathogens and free radicals. Further studies on genomic characterization of isolate and structure determination of the bioactive compounds are under progress.
Keywords: Agar well diffusion, DPPH, Streptomyces lydicus,Walailak University.